Ultra-high-pressure processing improves proteolysis and release of bioactive peptides with activation activities on alcohol metabolic enzymes in vitro from mushroom foot protein. (15th September 2017) - Zhao, Rui-Jie; Huo, Chun-Yan; Qian, Yang; Ren, Di-Feng; Lu, Jun
Highlights: Bioactive peptides were extracted from mushroom feet generally regarded as waste. Enzyme hydrolysis assisted with UHP increased soluble protein and hydrolysis degree. Low-molecular-weight peptides could activate alcohol metabolic enzymes in vitro. Abstract: This study was to find an effective process to extract bioactive peptides from mushroom foot and determine their effects on activation of alcohol metabolic enzymes in vitro. The optimum extraction assisted by ultra-high-pressure processing of mushroom foot peptides was obtained with a pressure of 400 MPa and a processing time of 10 min. After ultrafiltration, peptides with molecular weight of 0–3 kDa had the highest activity to activate alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) by 70.79% and 71.35%, respectively. Following dextran gel chromatography, two peaks (p-I and p-II) appeared and the activation activities on ADH and ALDH of p-I were 72.00% and 73.43%, both higher than p-II. Nine peptides were found in p-I as determined by LC–MS/MS, and two of them (IPLH and IPIVLL) were synthesized. IPLH activated ADH and ALDH by 42.7% and 29.2% respectively, which were higher than IPIVLL.